Musculoskeletal and mental health problems of adult (25-64 years) smokers of Dhaka city: a cross-sectional study (Asian Journal of Medical and Biological Research, 2023)
Both musculoskeletal and mental health are important components of the quality of life of individuals as well as public health. This study aimed to determine the musculoskeletal and mental health problems of adult smokers in Dhaka city, Bangladesh. During July to October 2022, a cross-sectional survey was conducted among desk-based officials in Dhaka city who smoke. Musculoskeletal pain of officials was determined by the Visual Analogue Scale (VAS), and mental health status was determined by the Patient Health Questionnaire (PHQ-9) scale. The collected dataset was checked and analyzed by IBM SPSS 23 package software. During the study period, 289 complete interviews with smokers were conducted, of which only 13.1% were female. Our analysis has identified a high prevalence of musculoskeletal pain (66%), where 15% had severe pain and another 28% had moderate pain. Severe depression was seen among 2.8% of participants, and another 9% had moderately severe depression. Advanced aged individuals (>54 years) are at higher risk of having musculoskeletal pain (OR=1.99, 95% CI: 1.01-3.93). People who are overweight or obese have 71% more risk of developing musculoskeletal pain (OR=1.71, 95% CI: 1.02-2.86). Moreover, having a lift facility in the house and the depression level of the participants were also significantly associated with the presence of musculoskeletal pain (P